Effects of plant growth regulators and explant types on callus formation in African yam bean (sphenostylis stenocarpa (hochst. Ex A. rich) harms) (2009)
This study was conducted to investigate the effect of explant types and plant growth regulator regimes on callus induction in African yam bean, with a view to developing protocols for regeneration Leaf, stem and root explants of African yam bean were cultured in media containing different types and concentrations of plant grow& regulators (PGR). The explants were observed for callus formation after three months. The main effects of variety, explant and plant growth regulator regimes and their interactions were highly significant Highest callus formation was recorded in stem explant while the root explant had the lowest. The accession, SSSWN56 brown seed) had higher percentage callus formation than ssswN7s (grey seed). No callus was formed in hormone-free medium and the media containing indole acetic acid (IAA). One- hundred-percent callus formation was recorded for both accessions in the medium containing 1.5 mg/l each of kinetin and Naphthalene acetic acid (NAA). This medium is recommended for callus induction using stem explant and it will be useful in perfecting regeneration protocols for African yarn bean.